Selective EGF-Receptor Inhibition in CD4 + T Cells Induces Anergy and Limits Atherosclerosis - Zeboudj, Lynda; Maître, Mikael; Guyonnet, Lea; Laurans, Ludivine; Joffre, Jeremie; Lemarie, Jeremie; Bourcier, Simon; Nour-Eldine, Wared; Guérin, Coralie; Friard, Jonas; Wakkach, Abdelilah; Fabre, Elizabeth; et al. (Journal of the American College of Cardiology, 2018)
Several epidermal growth factor receptor (EGFR) inhibitors have been successfully developed for the treatment of cancer, limiting tumor growth and metastasis. EGFR is also expressed by leukocytes, but little is known about its role in the modulation of the immune response. The aim of this study was to determine whether EGFR expressed on CD4 T cells is functional and to address the consequences of EGFR inhibition in atherosclerosis, a T cell-mediated vascular chronic inflammatory disease. The authors used EGFR tyrosine kinase inhibitors (AG-1478, erlotinib) and chimeric Ldlr Cd4-Cre/Egfr mouse with a specific deletion of EGFR in CD4 T cells. Mouse CD4 T cells expressed EGFR, and the EGFR tyrosine kinase inhibitor AG-1478 blocked in vitro T cell proliferation and Th1/Th2 cytokine production. In vivo, treatment of Ldlr mice with the EGFR inhibitor erlotinib induced T cell anergy, reduced T cell infiltration within atherosclerotic lesions, and protected against atherosclerosis development and progression. Selective deletion of EGFR in CD4 T cells resulted in decreased T cell proliferation and activation both in vitro and in vivo, as well as reduced interferon-γ, interleukin-4, and interleukin-2 production. Atherosclerotic lesion size was reduced by 2-fold in irradiated Ldlr mice reconstituted with bone marrow from Cd4-Cre/Egfr mice, compared to Cd4-Cre/Egfr chimeric mice, after 4, 6, and 12 weeks of high-fat diet, associated with marked reduction in T cell infiltration in atherosclerotic plaques. Human blood T cells expressed EGFR and EGFR inhibition reduced T cell proliferation both in vitro and in vivo. EGFR blockade induced T cell anergy in vitro and in vivo and reduced atherosclerosis development. Targeting EGFR may be a novel strategy to combat atherosclerosis.